2004
DOI: 10.1016/j.cub.2004.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for Netrins in Regulating Epithelial Behavior during Lung Branching Morphogenesis

Abstract: The development of many organs, including the lung, depends upon a process known as branching morphogenesis, in which a simple epithelial bud gives rise to a complex tree-like system of tubes specialized for the transport of gas or fluids. Previous studies on lung development have highlighted a role for fibroblast growth factors (FGFs), made by the mesodermal cells, in promoting the proliferation, budding, and chemotaxis of the epithelial endoderm. Here, by using a three-dimensional culture system, we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(155 citation statements)
references
References 30 publications
5
149
1
Order By: Relevance
“…Endogenous netrin-1, predominantly expressed by the floor plate cells in the central nervous system, induces axonal outgrowth, axonal orientation, and neuronal migration during neuronal development (Barallobre et al, 2005;Xie et al, 2006). Besides the aforementioned roles it plays in the central nervous system, NT-1 has also been implicated in regulating salivary gland migration (Kolesnikov and Beckendorf, 2005), regulating invasion and migration of mouse mammary epithelial cells (Strizzi et al, 2005), promoting lung branching morphogenesis (Liu et al, 2004), and mediating pancreatic epithelial cell adhesion (Hebrok and Reichardt, 2004). Further, netrin-1 can stimulate the proliferation and migration of human microvascular endothelial cells, and induce angiogenesis on chorioallantoic membrane and murine cornea in vivo (Park et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous netrin-1, predominantly expressed by the floor plate cells in the central nervous system, induces axonal outgrowth, axonal orientation, and neuronal migration during neuronal development (Barallobre et al, 2005;Xie et al, 2006). Besides the aforementioned roles it plays in the central nervous system, NT-1 has also been implicated in regulating salivary gland migration (Kolesnikov and Beckendorf, 2005), regulating invasion and migration of mouse mammary epithelial cells (Strizzi et al, 2005), promoting lung branching morphogenesis (Liu et al, 2004), and mediating pancreatic epithelial cell adhesion (Hebrok and Reichardt, 2004). Further, netrin-1 can stimulate the proliferation and migration of human microvascular endothelial cells, and induce angiogenesis on chorioallantoic membrane and murine cornea in vivo (Park et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The work of many laboratories has suggested that these cells are a multipotent epithelial progenitor population (reviewed in Cardoso and Lu, 2006). Compared with the epithelial stalk cells, the distal tip cells have a unique pattern of gene expression including high levels of Bmp4, Shh, Nmyc, Sox9, Id2, and Etv4/5 (reviewed in Rawlins, 2008), faster cell cycle kinetics (Okubo et al, 2005), and a subtly different morphology (Liu et al, 2004). Moreover, lung epithelial-specific deletion, or overexpression, of Nmyc results in phenotypes consistent with a premature loss, or overproliferation, of epithelial progenitor cells (Okubo et al, 2005).…”
Section: Multipotent Epithelial Progenitorsmentioning
confidence: 99%
“…Netrin-1 was the first to be purified and is the best-characterized member. In addition to its involvement in guiding axon migration during embryonic development, netrin-1 functions in organ formation [3][4][5][6] , tumorigenesis [7] , inflammation [8,9] , and anti-apoptotis [10] , as well as being a potential biomarker for renal injury and certain cancers [11,12] . It also promotes the recovery of neuronal function after cerebral ischemia in animal models [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%